Citra Kota Padang Dalam Puisi Padang Kota Tercinta Dan Perjalanan Senjakala Karya Leon Agusta (Tinjauan Semiotika Riffaterre) - Hayati, Fadhillah; Adilla, Ivan; Sudarmoko, Koko (Universitas Andalas, 2023)
One of the nicknames for Padang City is Padang Kota Tercinta. This name was born from a poem by Leon Agusta. Leon Agusta's poems that contain Padang Kota Tercinta, namely the poems entitled